2014
DOI: 10.1016/j.epsl.2014.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Seismically deduced thermodynamics phase diagrams for the mantle transition zone

Abstract: Seismic discontinuities at 410 and 660 km depth are usually attributed to solid phase changes within the olivine component of the mantle. The Clapeyron slopes γ 410 and γ 660 , i.e. the thermal dependence of the depths of reactions, have been shown experimentally to be of opposite signs. Yet, their values are not well constrained by laboratory measurements. Seismological observations have not been more precise due to the difficulty to separate the competing effects of background wave-velocities and of temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 56 publications
2
37
2
Order By: Relevance
“…Nevertheless, the values in Fig. S5a and b before correction are very low compared to other studies (Chevrot et al, 1999;Gao and Liu, 2014;Tauzin and Ricard, 2014). These poor correlation values probably indicate that depth changes are not controlled primarily by temperature changes and/or that the velocity structure in the upper-mantle and the TZ are anti-correlated with anomalies of the same order but opposite sign.…”
Section: Quantitative Analysis Of Time Corrections and Discontinuity contrasting
confidence: 65%
See 2 more Smart Citations
“…Nevertheless, the values in Fig. S5a and b before correction are very low compared to other studies (Chevrot et al, 1999;Gao and Liu, 2014;Tauzin and Ricard, 2014). These poor correlation values probably indicate that depth changes are not controlled primarily by temperature changes and/or that the velocity structure in the upper-mantle and the TZ are anti-correlated with anomalies of the same order but opposite sign.…”
Section: Quantitative Analysis Of Time Corrections and Discontinuity contrasting
confidence: 65%
“…Nevertheless, the mantle structure leads to large positive correlation of the observed depth values (and relative travel times), e.g., +0.94 in Chevrot et al (1999), +0.84 in Gao and Liu (2014), and +0.6 in Tauzin and Ricard (2014). Ideally, a negative or near zero correlation value is expected after correction, but in practice it is observed that velocity corrections reduce the correlation to smaller positive values (e.g., Gao and Liu, 2014;Tauzin, 2009).…”
Section: Quantitative Analysis Of Time Corrections and Discontinuity mentioning
confidence: 91%
See 1 more Smart Citation
“…Assuming homogeneous composition, we expect that the MTZ is thicker than normal at low temperature and thinner than normal at high temperature. apparent depths of discontinuities and introduce a positive correlation that is opposite to the temperature effect (e.g., Tauzin & Ricard, 2014). However, this ideal picture may be complicated by several effects.…”
Section: 1029/2018gl081742mentioning
confidence: 99%
“…Using equations and and assuming a vertical incidence ( p = 0) of the ray, the “true” depth of the discontinuity d can be expressed as d=truetrue∫0dAVs()zVs_normalrnormalenormalf()znormaldz=truetrue∫0dAVs_normalrnormalenormalf()z+dv()zVs_normalrnormalenormalf()znormaldz where dv ( z ) is the depth‐varying S wave velocity anomaly, which can be obtained from seismic tomography models. We adopted this simple 3‐D velocity correction to obtain the true depth of discontinuities, in the same manner as performed by some receiver function studies [ Gao and Liu , ; Tauzin and Ricard , ].…”
Section: Application To Japan Sea Regionmentioning
confidence: 99%